1986
DOI: 10.1212/wnl.36.7.998
|View full text |Cite
|
Sign up to set email alerts
|

MRI periventricular lesions in adults

Abstract: We studied MRI findings of a periventricular high-signal intensity pattern in 151 adults older than 50 years. Only 7.8% of patients who had no identified cerebrovascular risk factors and who reported no cerebrovascular symptoms had these MRI periventricular lesions; 78.5% of patients with a history of cerebrovascular risk factors and who had had cerebrovascular symptoms had periventricular patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
60
2
7

Year Published

1987
1987
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(78 citation statements)
references
References 0 publications
9
60
2
7
Order By: Relevance
“…This does not mean, however, that the grey matter structures are affected with no consequence to their associated fiber tracts, but only that such consequences may be manifested as signal changes w.%hin the white matter rather than shrinkage. These observed signal changes in the white matter agree with earlier reports of an increasing incidence of visually identified high signal areas in the elderly (Gerard and Weisberg 1986;Awad et al 1986aAwad et al , 1986bAwad et al , 1987Fazekas et al 1987;Kertesz et al 1988). The age function reported here for the index of white matter abnormality is quite similar to that obtained with our measure of subcortical hyperintensities (Jemigan et al 1990).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This does not mean, however, that the grey matter structures are affected with no consequence to their associated fiber tracts, but only that such consequences may be manifested as signal changes w.%hin the white matter rather than shrinkage. These observed signal changes in the white matter agree with earlier reports of an increasing incidence of visually identified high signal areas in the elderly (Gerard and Weisberg 1986;Awad et al 1986aAwad et al , 1986bAwad et al , 1987Fazekas et al 1987;Kertesz et al 1988). The age function reported here for the index of white matter abnormality is quite similar to that obtained with our measure of subcortical hyperintensities (Jemigan et al 1990).…”
Section: Discussionsupporting
confidence: 91%
“…Q signal hyperintensities within the white matter were also app These measures revealed significant increases in these abnorma a finding noted in qualitative evaluations of normal elderly subjects by several investigators (Gerard and Weisberg 1986;Awad et al 1986aAwad et al , 1986bFazekas et al 1987;Kertesz et al 1988). The present study further describes the age-related changes in brain structure, focusing on specific cerebral grey matter structures, both cortical and subcortical, in adults between 30 and 79 years of age.…”
Section: Ictroductionsupporting
confidence: 75%
“…The same lesion was often observed in the clinically healthy aged human brain. Gerard and Weisherg [19] reported that 7.8% of human over age 50 years showed perivascular hyper-intensity area on T2-weighted images without symptoms of cerebrovascular disease. The area was resulted from the changes of myelin structure with fluid-filled space in white matter [19,29].…”
Section: Discussionmentioning
confidence: 99%
“…Gerard and Weisherg [19] reported that 7.8% of human over age 50 years showed perivascular hyper-intensity area on T2-weighted images without symptoms of cerebrovascular disease. The area was resulted from the changes of myelin structure with fluid-filled space in white matter [19,29]. Since the degeneration of white mater was reported in dogs aged more than 14-year-old [18], the hyper-intensity area on T2-weigted images was considered to be one of the ageassociated changes in white matter in the dog brain, although the area observed in beagle dogs was slightly mild compared with that in the human.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies of AD with MR have emphasized the prevalence and appearance of high signal abnormalities in cortical and subcortical ;auc- (Johnson et al 1987;Fazekas et al 1987), the high incidence of these abnormalities i~: nonsymptomatic elderly controls (Fazekas et al 1987;Gerard and Weisberg 1986;Awad et al 1986aAwad et al , 1986bAwad et al , 1987Kertesz et al 1988) complicates the interpretation of such changes in AD. Attempts to differentiate AD patients from controls and other patients using MR signal values within tissue, such as Tt and proton density values, have met wtth mixed success (Besson et al 1983(Besson et al , 1985Christie et al 1988).…”
Section: Introductionmentioning
confidence: 99%